Network Effects in Railways - Landex, Alex; Nielsen, Otto Anker (Proceedings from the Annual Transport Conference at Aalborg University, 2007)
Railway operation is often affected by network effects as a change in one part of the network can influence other parts of the network. This influence can even be far away from where the original change was made. The network effects occur because the train routes (often) are quite long and that the railway system has a high degree of interdependencies as trains cannot cross/overtake each other everywhere in the network. First the article describes network effects in general (section 2). In section 3 the network effects for trains – and how they can be measured by queuing time is described. When the trains are affected by network effects also the passengers are affected. Therefore, section 4 describes the network effects for passengers and how they can be measured using passenger delay models. Before the concluding remarks in section 6, section 5 discusses how the operation can be improved by examining network effects in the planning process.